Закон керування електроприводом візка мостового крану із розгоном у три етапи та варіацією прискорення - Толочко, Ольга Іванівна; Бажутін, Денис Володимирович (НТУ "ХПІ", 2010)
This article is to deal with anti-swing control algorithm of an overhead crane trolley electric drive. A three-stage speedup tachogram with variable acceleration is discussed. Expressions for time intervals evaluation are given. The effectiveness analysis of such control algorithm concerning positioning time and motor heat losses is considered.
Control algorithm for an overhead crane trolley electric drive with three stage speedup and variable acceleration
Keywords: коливання; момент двигуна; прискорення; гальмування; модель математична; витрати теплові